2020
DOI: 10.1080/10410236.2020.1847449
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Information-seeking in an Age of COVID-19: Findings from the National Cancer Institute’s Cancer Information Service

Abstract: Seeking cancer information is recognized as an important, life-saving behavior under normal circumstances. However, given the significant impact of COVID-19 on society, the healthcare system, and individuals and their families, it is important to understand how the pandemic has affected cancer information needs in a crisis context and, in turn, how public health agencies have responded to meeting the information needs of various audiences. Using data from the National Cancer Institute's Cancer Information Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…Our findings are consistent with the findings of a recent study by the National Cancer Institute (NCI) that found, during the early months of the COVID-19 pandemic, cancer survivors and caregivers were more likely to engage with NCI’s Cancer Information Services resources than tobacco users or the general public. This pattern was consistent for English- and Spanish-speaking users accessing content via telephone, instant messaging, email, and social media [ 41 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our findings are consistent with the findings of a recent study by the National Cancer Institute (NCI) that found, during the early months of the COVID-19 pandemic, cancer survivors and caregivers were more likely to engage with NCI’s Cancer Information Services resources than tobacco users or the general public. This pattern was consistent for English- and Spanish-speaking users accessing content via telephone, instant messaging, email, and social media [ 41 ].…”
Section: Discussionmentioning
confidence: 64%
“…RenderX was consistent for English-and Spanish-speaking users accessing content via telephone, instant messaging, email, and social media [41].…”
Section: Xsl • Fomentioning
confidence: 84%
“…However, in the second phase, the media's agenda-setting capabilities did not function nearly as well when their agenda was of little relevance to the concerns of the public, neither addressing nor catering to the demand for cancer information among the population over the last five years. This was especially the case in 2020 when the gap widening was accelerating, and the causal linkages between the attention from both the public and media were substantially fractured, as cancer information-seeking was quite likely heightened when under the conditions of an epidemic [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the second half phase, the media's agendasetting capabilities did not function nearly as well when their agenda was of little relevance to the concerns of the public, neither addressing nor catering to the demand for cancer information among the population over the last five years. This was especially the case in 2020 where the gap widening was accelerating as it appeared and the causal linkages between the attention from both the public and media substantially fractured, when under the conditions of an epidemic, cancer information-seeking was quite likely heightened [37,38].…”
Section: Discussionmentioning
confidence: 99%